Measuring Performance of Digital Projects: Case of Swiss Medium-sized Enterprises - Klinkert, Thierry André; Meyer , Mona A.; Nainggolan, Yunieta Anita (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
The research objective is to understand the challenges of digitalisation of Swiss medium-sized enterprises and their satisfaction with current measurement methods, and to develop a measurement model to evaluate the performance of their digital projects. The research methodology involved a comprehensive literature review, followed by interviews with experts from 15 medium sized companies. The analysis revealed that Swiss medium sized enterprises not only lack the appropriate tools to measure their digital projects’ performance but are also facing challenges caused by the lack of financial resources and time to implement digital projects; and the difficulty of finding the right people to execute digital projects. The results from the research include a measurement model for digital projects. This model supports managers in making effective decisions regarding their digital projects, allocating resources more effectively, and enhancing overall organizational performance. The research outcomes are not necessarily generalizable to other enterprises (other size, other nations). However, they show that in the context of digital projects, Swiss medium-sized companies need a measurement model to evaluate the performance and success since such technologies/projects are associated with financial costs. For future research, the developed model should be tested with different firms in an operational handling where effective past or future projects would be measured. This could further explore the applicability of the model to different sized enterprises or those in other nations.